The rise of invariability in the Low Lithuanian reflexive participles and verbal nouns - Petit, Daniel (Baltistica, 2014)
In the Low Lithuanian dialects reflexive half-participles and verbal nouns are indeclinable and display a unique ending -damos, resp. -imos. The aim of this paper is to explain the invariability of these forms, which represents a striking feature of Low Lithuanian. It is proposed that invariability in the verbal nouns in -imos derives from their neuter origin, whereas in the half-participles in -damos it results from complex processes of phonological merging. In both cases, the preservation of invariability is due to the overall difficulty of building reflexive nominal forms of the verbs.